NINETEENTH CENTURY REVIS(IT)ED the new historical fiction. - Bergmann, Ina. ([S.l.] : ROUTLEDGE, 2020)
The Nineteenth Century Revis(it)ed: The New Historical Fiction explores the renaissance of the American historical novel at the turn of the twenty-first century. The study examines the revision of nineteenth-century historical events in cultural products against the background of recent theoretical trends in American studies. It combines insights of literary studies with scholarship on popular culture. The focus of representation is the long nineteenth century - a period from the early republic to World War I - as a key epoch of the nation-building project of the United States. The study explores the constructedness of historical tradition and the cultural resonance of historical events within the discourse on the contemporary novel and the theory formation surrounding it. At the center of the discussion are the unprecedented literary output and critical as well as popular success of historical fiction in the USA since 1995. An additional postcolonial and transatlantic perspective is provided by the incorporation of texts by British and Australian authors and especially by the inclusion of insights from neo-Victorian studies. The book provides a critical comment on current and topical developments in American literature, culture, and historiography.
OCLC-licensed vendor bibliographic record.
Keywords: Historical fiction, American -- 21st century -- History and criticism; LITERARY CRITICISM / General